2020
DOI: 10.1177/0969141320930743
|View full text |Cite
|
Sign up to set email alerts
|

Systematic reviews as a “lens of evidence”: Determinants of participation in breast cancer screening

Abstract: Objective To assess the determinants of the participation rate in breast cancer screening programs by conducting a systematic review of reviews. Methods We conducted a systematic search in PubMed via Medline, Scopus, Embase, and Cochrane identifying the literature up to April 2019. Out of 2258 revealed unique abstracts, we included 31 reviews, from which 25 were considered as systematic. We applied the Walsh & McPhee Systems Model of Clinical Preventive Care to systematize the determinants of screening par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…A pre‐scheduled appointment is known to increase participation in screening for breast cancer 38 . Similarly, we found that our participants recommended offering a pre‐scheduled appointment, although concern was expressed about the risk of violating the invitees' autonomy.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…A pre‐scheduled appointment is known to increase participation in screening for breast cancer 38 . Similarly, we found that our participants recommended offering a pre‐scheduled appointment, although concern was expressed about the risk of violating the invitees' autonomy.…”
Section: Discussionmentioning
confidence: 63%
“…36,37 A pre-scheduled appointment is known to increase participation in screening for breast cancer. 38 Similarly, we found that our participants recommended offering a pre-scheduled appointment, although concern was expressed about the risk of violating the invitees' autonomy. However, legally, a screening invitation must stress that participation is optional and that whether the invitation is accepted or not is without consequences for the invitees' current treatment.…”
Section: Nudging As a Strategy For Participation In Screeningmentioning
confidence: 79%
“…As recommended in a previous study, 20,25 the composite fear score on the CBCFS was computed using three categories (strongly agree/agree, strongly disagree/disagree, and undecided). Next, the fear score was stratified into low (8)(9)(10)(11)(12)(13)(14)(15), moderate (16)(17)(18)(19)(20)(21)(22)(23), or high fear (24-40) categories. 25 Similarly, the perceived selfefficacy for mammography score was stratified into low (10)(11)(12)(13)(14)(15)(16)(17)(18)(19), moderate (20)(21)(22)(23)(24)(25)(26)(27)(28)(29), or high fear (30-50) categories.…”
Section: Discussionmentioning
confidence: 99%
“…Next, the fear score was stratified into low (8)(9)(10)(11)(12)(13)(14)(15), moderate (16)(17)(18)(19)(20)(21)(22)(23), or high fear (24-40) categories. 25 Similarly, the perceived selfefficacy for mammography score was stratified into low (10)(11)(12)(13)(14)(15)(16)(17)(18)(19), moderate (20)(21)(22)(23)(24)(25)(26)(27)(28)(29), or high fear (30-50) categories. To examine associations between fear, perceived self-efficacy, demographic characteristics, and BCS (ie, CBE and mammographic screening), both bivariate and multivariable logistic regression models were used.…”
Section: Discussionmentioning
confidence: 99%
“…Within the broader literature, studies have found that lower uptake of preventive care is associated with lower levels of education, health literacy and household income, as well as a lack of usual source of healthcare provider, health insurance coverage and migrant status ( Carney and O’Neill, 2018 , Sambamoorthi and McAlpine, 2003 , Mandrik et al, 2021 , Norredam et al, 2010 ). Various other factors have also been shown to influence an individual’s use of preventive care.…”
Section: Introductionmentioning
confidence: 99%